Doña Barbara - Gallegos, Rómulo, 1884-1969 (The University of Chicago Press, 2012)
Dona Barbara tells the tale of an epic struggle between two cousins for a cast estate and ranch in the Venezuelan llano, or prairie ... Published in 1929 and all but forgotten by Anglophone readers, Dona Barbara is one of the first examples of magical realism, laying the groundwork for later authors such as Gabriel Garcia Marquez and Mario Vargas Llosa.